Emotional dysfunction associated with diabetes in Mexican adolescents and young adults with type-1 diabetes - Lerman-Garber Israel; Barrón-Uribe Consuelo; Calzada-León Raúl; Mercado-Atri Moisés; Vidal-Tamayo Rafael; Quintana Silvia; Hernández María Elena; Ruiz-Reyes María de la Luz; Tamez-Gutiérrez Laura Elena; Nishimura-Meguro Elisa; Villa Antonio R (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To assess the emotional dysfunction associated with diabetes in Mexican young individuals with type-1 diabetes. MATERIAL AND METHODS: A cross-sectional survey was conducted to perform a complete clinical and psychosocial evaluation of 93 consecutive type-1 diabetes patients, aged 14 to 30 years. RESULTS: Adolescents had higher scores of emotional dysfunction related to diabetes and a diminished knowledge in diabetes-related areas. A multivariate logistic regression model showed that an inadequate emotional response to diabetes (high problem areas in diabetes or PAID scores) was mainly associated with a poor glycemic control (OR=2.9, 95% CI 0.9-9.7, p=0.09). Apprehension about the future and the possibility of serious complications had the highest mean PAID score in all age groups. CONCLUSIONS: New strategies should be developed to improve the routine care and support of young individuals with type-1 diabetes.